Effect of Timing of Branched-Chain Amino Acid Supplementation on Muscle Recovery after Resistance Training in Healthy Males - Kebin Meng (American Journal of Men's Health)
This study aimed to investigate the effects of different timing of branched-chain amino acid (BCAA) supplementation (pre-/post-exercise) on the recovery of delayed-onset muscle soreness (DOMS) and associated inflammatory factors after resistance training. A double-blind randomized controlled experimental design was used in this study. Twenty-four untrained male college students volunteered to receive BCAA supplementation and completed resistance training. Participants were randomly assigned to the BCAA and placebo groups and sequentially performed two experiments of pre-exercise supplementation and post-exercise supplementation. Thus, four groups were formed: the BCAA-PRE group, the BCAA-POST group, the PLCB-PRE group, and the PLCB-POST group. Muscle soreness, countermovement jump (CMJ), and related blood parameters [interleukin-6 (IL-6), C-reactive protein (CRP), creatine kinase (CK), blood lactate (B[La])] were measured 30 min, 24 and 48 hr after resistance training. BCAA post-exercise supplementation significantly reduced muscle soreness scores compared to the placebo group at 48 hr after resistance training ( p  < .05). At 24 hr after resistance training, the BCAA group significantly reduced serum IL-6 and CRP ( p  < .05), in addition, the BCAA-POST group had lower serum IL-6 and CRP than the BCAA-PRE group ( p  < .05). No significant difference between groups was detected for CMJ or B[La] ( p  > .05). Resistance training induced the development of DOMS accompanied by elevated inflammatory factors (CRP and IL-6) and muscle proteins (CK). Compared to pre-exercise BCAA supplementation, post-exercise supplementation was observed to be more effective in alleviating the symptoms of DOMS and reducing inflammatory factors. However, it does not change the state of neuromuscular recovery.